(untitled) (Journal of Namibian Studies : History Politics Culture, 2022)
Chronic Obstructive Pulmonary Disease (COPD) imposes a significant burden on patients and healthcare systems globally. This progressive lung condition requires comprehensive assessment and treatment strategies to manage symptoms, prevent exacerbations, and improve quality of life. Medical doctors and nurses play pivotal roles in the care of individuals with COPD. Doctors, particularly pulmonologists, conduct thorough assessments, diagnose COPD, and develop personalized treatment plans, including medication management and lifestyle modifications. Nurses support this process by assisting in assessments, providing patient education, and monitoring treatment adherence and symptom management. Both healthcare professionals collaborate closely to ensure continuity of care and optimize outcomes for patients with COPD. This abstract highlights the crucial roles of medical doctors and nurses in the assessment and treatment of COPD, emphasizing the importance of multidisciplinary care in managing this chronic condition effectively.